2020
DOI: 10.3390/ani10020294
|View full text |Cite
|
Sign up to set email alerts
|

Indicators of Horse Welfare: State-of-the-Art

Abstract: Animal welfare is defined as a chronic state reflecting an individual’s subjective perception of its situation. Because it is possible to be in a good welfare state and nevertheless experience acute fear or pain, and conversely, short-term positive emotions can be experienced during impaired welfare states, welfare as a chronic state has to be clearly distinguished from temporary states related to emotions, pain or stress. The evaluation of non-verbal individuals’ welfare state, particularly in interspecific s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
114
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 109 publications
(120 citation statements)
references
References 133 publications
1
114
0
5
Order By: Relevance
“…A review of animal-based indicators and proposals can be found in Lesimple [1]; thus, we will evoke here only a few examples.…”
Section: Welfare Indicatorsmentioning
confidence: 99%
See 2 more Smart Citations
“…A review of animal-based indicators and proposals can be found in Lesimple [1]; thus, we will evoke here only a few examples.…”
Section: Welfare Indicatorsmentioning
confidence: 99%
“…Although the question of animal welfare has been a source of concern in the scientific community and of attempts to build communal protocols over the last decades, many aspects are still under debate, such as the validity and reliability of the welfare indicators chosen (e.g., [1]). This is especially the case for on-farm assessments, i.e., evaluation of welfare at a facility population level, for which scientists may have felt forced to answer public concerns rapidly, hence producing suboptimal criteria [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Concerns about anthropomorphic reasoning have led, among other things, to skepticism regarding whether or not animals can experience pain in ways that cause them to suffer (e.g., [25,26]), and whether mammals other than human beings can be shown unequivocally to have any conscious experiences at all, including pain experience (e.g., [27,28]). Such concerns also underlie an apparent hesitation, reluctance, or extreme caution among some scientists to accept that animals can have a wide range of observable subjective experiences, including pain, which are of significance to their welfare (e.g., in horses [28,29]), despite a large body of supporting literature to the contrary (Section 2.3).…”
Section: Cerebrocortical Involvement In the Conscious Experience Of Pmentioning
confidence: 99%
“…HR is considered as a measure of stress in animals because it reflects the ratio between the vagal (which reduces HR) and the sympathetic tone of ANS (which increases HR) [ 52 , 53 , 54 , 55 ]. At rest, vagal regulation dominates, but the influence of the sympathetic components of ANS increases with physical activity.…”
Section: Introductionmentioning
confidence: 99%